Pengaruh Literasi Keuangan, Inklusi Keuangan Dan Pengelolaan Keuangan Terhadap Kinerja Dan Keberlangsungan Teknologi Keuangan Sebagai Variabel Moderasi - Uci Asyifa; Deni Dermawati (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
A superior performance in sustainable business can be realized if there are efforts in determining strategy. DKI Jakarta is one of the provinces with a large number of UMKM which has great opportunities to improve the Indonesian economy. This research was conducted to analyze the influence of financial literacy, financial inclusion and financial management on business performance and sustainability with financial technology as a moderating variable. This research is a quantitative research with a sample of 75 UMKM which were then analyzed using the Partical Least Square (PLS) approach. The results conclude that Financial Inclusion has an influence on Business Sustainability, Financial Management has an influence on the performance of UMKM and Financial Management has a positive and significant influence on the Business Sustainability of UMKM.